Primary Ewing sarcoma of the larynx with distant metastasis: a case report and review of the literature - Maroun, C.A. (Curr Oncol, 2019)
Extraosseous Ewing sarcoma is a rare, poorly differentiated round-cell tumour that is part of the Ewing sarcoma family of tumours. Here, we present an extremely rare case of primary extraosseous Ewing sarcoma arising in the larynx, with distant metastases. A 53-year-old man with a history of Hodgkin lymphoma treated 4 years earlier with 8 cycles of chemotherapy presented to our medical centre with a 2-week history of hoarseness. On physical examination, he was found to have a right supraglottic mass together with a fixed right vocal cord. Computed tomography imaging of the patient’s neck showed a heterogeneously enhancing lesion measuring 5.0×3.8×3.8 cm, centred on the right thyroid cartilage and invading the right true vocal cord. Imaging by integrated fluorodeoxyglucose positron-emission tomography and computed tomography showed active subcarinal and axillary lymph nodes, multiple scattered lung nodules, and multiple bony metastases. Needle core biopsy of the laryngeal mass was diagnostic for Ewing sarcoma. The patient received radiation to the laryngeal area and then alternating cycles of vincristine–actinomycin-D–cyclophosphamide and etoposide–ifosfamide. The patient remains in remission 1 year after completing therapy. As demonstrated in the present report, these tumours can behave very aggressively both locally and by metastasizing to distant organs. Our treatment approach provided favourable results for the patient; however, future reports are needed to further elucidate optimal management.